The questions of interaction between state and religion and it’s values (Journal of Oriental Studies, 2016)
in this article raises questions of interaction between state and religion; regulate their activities, learning experiences of other countries on the regulation of interaction between state and religion, their past, present and future is explored.
Keywords: religion; charismatic; policy